2001
DOI: 10.1007/pl00002939
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for renal failure: The WHO multinational study of vascular disease in diabetes

Abstract: Diabetes accounts for one third or more of all new end stage renal disease in the United States and accounts for at least 16 % of all new patients going onto renal replacement therapy in Europe [1]. The most common cause of end stage renal disease in diabetes is diabetic glomerulosclerosis (nephropathy).Previous studies have shown that hyperglycaemia is an important risk factor for diabetic renal disease [2,3]. More controversy exists on the extent to which systolic blood pressure and lipid disturbances are ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 28 publications
2
44
0
Order By: Relevance
“…It is of note that total cholesterol remained an independent predictor even after the inclusion of eGFR. In the WHO MSWDD study, triacylglycerol was predictive of renal failure in patients with type 2 diabetes, but not in patients with type 1 diabetes [30]. However, this could have been because of the power, since the number of progressors was lower and triacylglycerol was only measured in a sub-sample of patients.…”
Section: Discussionmentioning
confidence: 96%
“…It is of note that total cholesterol remained an independent predictor even after the inclusion of eGFR. In the WHO MSWDD study, triacylglycerol was predictive of renal failure in patients with type 2 diabetes, but not in patients with type 1 diabetes [30]. However, this could have been because of the power, since the number of progressors was lower and triacylglycerol was only measured in a sub-sample of patients.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies of type 2 diabetes have shown an association between CKD, proteinuria and cardiovascular disease (CVD) prevalence [3] and risk [4][5][6][7][8][9][10][11]. However, many of these studies were small and did not examine the independent effects of microalbuminuria, macroalbuminuria and eGFR.…”
Section: Introductionmentioning
confidence: 99%
“…603933, available at http://www.ncbi.nlm.nih.gov/omim) is a common microvascular complication of type 1 and type 2 diabetes. Increasing prevalence of diabetic nephropathy and end-stage renal disease (ESRD) attributed to diabetes have been observed, particularly in older adults (1)(2)(3). In 1999 -2003, the estimated prevalence of type 2 diabetes among all ESRD patients in the U.S. was ϳ29.1%, but among new ESRD cases during the same period, it was 40.5% (1).…”
mentioning
confidence: 99%